Neuroprotective effect of S-allyl-l-cysteine derivatives against endoplasmic reticulum stress-induced cytotoxicity is independent of calpain inhibition - Toru Imai; Yasuhiro Kosuge; Hiroaki Saito; Taketo Uchiyama; Taira Wada; Shigeki Shimba; Kumiko Ishige; Shinichi Miyairi; Makoto Makishima; Yoshihisa Ito (Elsevier, 2016)
S-allyl-l-cysteine (SAC) is known to have neuroprotective properties. We synthesized various SAC derivatives and tested their effects on endoplasmic reticulum stress-induced neurotoxicity in cultured hippocampal neurons (HPNs). Among the compounds tested, S-propyl-l-cysteine (SPC) exhibited the strongest neuroprotective activity in HPNs, followed by S-ethyl-l-cysteine (SEC) and S-methyl-l-cysteine (SMC). Unlike SAC and SMC, SPC and SEC did not have inhibitory activity on μ-calpain, suggesting that the mechanism underlying the protective activity of SPC and SEC differs from that of SAC.